Macroeconomic determinants of Malaysian stock market: case in KLCI / Muhammad Arif Ab Samah - Ab Samah, Muhammad Arif (Faculty of Business Management, 2014)
The purpose of this research is to determine the significant relationship between macroeconomics variables and the stock equity market in Malaysia. The researcher will use Kuala Lumpur Composite Index as the main indicator for dependent variables and the macroeconomic variables comprises of money supply, industrial production, gross domestic product, inflation rate and interest rate. In order to determine the relationship between the five (5) macroeconomics variable and the Kuala Lumpur Composite Index (KLCI), this project paper used quarterly basis during the period from 2004-2013 and E-views software is applied to analyze it. The scope of study for the research is within Malaysia. A part from that, this study employs proxy to a few of the selected macroeconomic variables such as KLCI for stock index, BLR for interest rate, CPI for inflation rate and M2 for money supply. Therefore, the data analysis plan for this research is Multiple Linear Regression Model in order to analyze the data. Based on the previous study, it was found that two of the economic variables, interest rate and inflation rate have a negative relationship towards the KLCI while money supply and GDP have negative relationship towards KLCI. Additionally, in contrast with the above study, the researcher found out there are past research claims that all independent variable is significant with all macroeconomic variables therefore all the independent variable have positive relationship with dependent variable.